PURCHASE INTENTION OF OMG-EVENT-ASIA’S: HOW SOCIAL MEDIA PROMOTIONS EFFECT THROUGH BRAND AWARENESS - Lutfie, Harrie; Marcelino, Dandy (Dinasti Publisher, 2020)
The development of information and communication technology has been so rapid since the emergence of the internet, especially social media. The use of social media has developed into a way for event organizers to do social media marketing to introduce their consumers through electronic media, one of the applications has been carried out by OMG Event Asia. This study aims to identify and measure the effectiveness of promotional strategies through social media that have been carried out by the event organizer in generating brand awareness and buying interest from potential customers. The results of research conducted that promotion through social media has a significant relationship to brand awareness and purchase interest. Event organizer companies can carry out promotions through social media with clear target segments related to product functions. Submission of information about the product must be in detail related to quality, price, and social value to the target segment.